The association between reproductive and hormonal factors and ovarian cancer by estrogen-α and progesterone receptor status - Shafrir, Amy L. (Gynecol Oncol, 2016)
OBJECTIVE: We assessed the association between reproductive and hormonal factors and ovarian cancer incidence characterized by estrogen receptor-α (ERα) and progesterone receptor (PR) status. METHODS: Tissue microarrays were used to assess ERα and PR expression among 197 Nurses’ Health Study (NHS), 42 NHSII and 76 New England Case-Control Study (NECC) ovarian cancer cases. NHS/NHSII cases were matched to up to 4 controls (n=954) on diagnosis date and birth year. NECC controls (n=725) were frequency matched on age. Cases were considered receptor positive if ≥1% of tumor cells stained positive. Associations by ERα and PR status were assessed using polytomous logistic regression. P-value for heterogeneity was calculated using a likelihood ratio test. RESULTS: 45% of ovarian tumors were PR+, 78% were ERα+ and 45% were ERα+/PR+, while 22% were ERα−/PR−. Postmenopausal status was associated with an increased risk of PR− tumors (OR: 2.07; 95%CI: 1.15–3.75; p-heterogeneity=0.01) and age at natural menopause was inversely associated with PR− tumors (OR, per 5yr: 0.77; 95%CI: 0.61–0.96; p-het=0.01). Increasing duration of postmenopause was differentially associated by PR status (p-het=0.0009). Number of children and tubal ligation were more strongly associated with ERα− versus ERα+ tumors (p-het=0.002 and 0.05, respectively). No differential associations were observed for oral contraceptive or hormone therapy use. CONCLUSIONS: Postmenopausal women have an increased risk of developing PR− ovarian tumors compared to premenopausal women. The associations observed for ovarian cancer differ from those seen for breast cancer suggesting that the biology for tumor development through ERα and PR pathways may differ.